Improving creativeness of computer games produced by students through appreciative learning approach - Wan Ali, Wan Zah; Eow, Yee Leng; Mahmud, Rosnaini; Baki, Roselan (2011)
Both computer games development and appreciative learning approach are still in their early evolutions at educational setting. By ignoring the educational power of computer games development and appreciative learning approach, educationist could risk losing a valuable tool and pedagogical strategy. Therefore, this study attempted to investigate the effectiveness of appreciative learning approach and computer games development combination in enhancing students creativity in terms of the products produced. The study applied randomised subjects, with control group experimental design and involved 69 Malaysian from one (grade seven) student, aged 13-14 year-old. Computer Game Assessment Inventory (COMGAIN) was created specifically to assess the product's creativity in terms of the computer games produced by students. It generated a Cronbach's Alpha value .726. It was found students in treatment group exhibited a mean score of 6.62, which was significantly higher at .05 level of significance compared to the mean score 5.35 exhibited by the control group. Therefore, computer games development and appreciative learning approach combination offers a great opportunity for improving the creativeness of computer games produced by students. Nevertheless, computer games produced by students have more rooms for improvements.